Pengembangan Media Pembelajaran Pop Up Book Berbasis Model ARIAS di Kelas III Sekolah Dasar - Chintya Oktaviani; Risda Amini (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to develop Pop Up Book learning media in integrated thematic learning that is valid and practical. The type of research conducted is Research and Development (R&D) using the ADDIE development model with the Analysis, Design, Development, Implementation, Evaluation stages. Data collection uses a validation sheet, and a response questionnaire. Where the validation sheet consists of material expert validation sheets, media expert validation sheets and linguist validation sheets. The results of research on the development of Pop Up Book learning media were developed through the validation stages of material aspects, media aspects, and language aspects. In the material aspect, it shows 87.5% valid category. In the media aspect, the percentage of 96% is very valid, and in the language aspect, the percentage is 93.7%, the category is very valid. While the practicality test at the trial stage for students obtained an average score of 91% and the practicality of the teacher obtained an average score of 92% with a very practical category. For the results of the practicality of the implementation phase, teachers get an average score of 96%, and students get an average score of 93% (very practical category).